Climate change risk assessments in value chain projects - International Fund for Agricultural Development (2015)
Successful value chain interventions that achieve poverty reduction goals can in themselves be beneficial to climate change adaption, as they build farmers’ assets and institutional linkages. But climate change can have major effects on the outcomes of IFAD-supported value chain interventions for smallholder beneficiaries; these outcomes may be negative or positive, and in many cases are uncertain. Therefore, it pays to do a simple upfront risk assessment to identify and manage risks and opportunities. The purpose of this How To Do Note (HTDN) is to provide guidance on the basics of climate risk analysis for value chain interventions.